Correlation of precisely fabricated geometric characteristics of DNA-origami nanostructures with their cellular entry in human lens epithelial cells - Yexuan Guo; Tianze Xiong; Hong Yan; Rui Xue Zhang (Discover Nano)
Abstract Human lens epithelial cells (hLECs) are critical for lens transparency, and their aberrant metabolic activity and gene expression can lead to cataract. Intracellular delivery to hLECs, especially to sub-cellular organelles (e.g., mitochondrion and nucleus), is a key step in engineering cells for cell- and gene- based therapies. Despite a broad variety of nano- and microparticles can enter cells, their spatial characteristics relevant to cellular uptake and localization remains elusive. To investigate cellular internalization of nanostructures in hLECs, herein, DNA nanotechnology was exploited to precisely fabricate four distinct, mass-controlled DNA-origami nanostructures (DONs) through computer-aided design. Ensembled DONs included the rods, ring, triangle, and octahedron with defined geometric parameters of accessible surface area, effective volume, compactness, aspect ratio, size and vertex number. Atomic force microscopy and agarose gel electrophoresis showed that four DONs self-assembled within 3.5h with up to 59% yield and exhibited structural intactness in cell culture medium for 4 h. Flow cytometry analysis of four Cy5-labelled DONs in hLECs HLE-B3 found time-dependent cellular uptake over 2 h, among which the octahedron and triangle had higher cellular accumulation than the rod and ring. More importantly, the vertex number among other geometric parameters was positively correlated with cellular entry. Confocal images further revealed that four DONs had preferential localization at mitochondria to nucleus at 2 h in HLE-B3 cells, and the degree of their biodistribution varied among DONs as evidenced by Manders’ correlation coefficient. This study demonstrates the DONs dependent cellular uptake and intracellular compartment localization in hLECs, heralding the future design of structure-modulating delivery of nanomedicine for ocular therapy. Graphical abstract